2020
DOI: 10.1186/s12913-020-05247-w
|View full text |Cite
|
Sign up to set email alerts
|

Community based programs to improve the oral health of Australian Indigenous adolescents: a systematic review and recommendations to guide future strategies

Abstract: Background: To review the international literature on community-based interventions aiming to improve the oral health of Indigenous adolescents and identify which demonstrate a positive impact. Methods: Data sources were MEDLINE, EMBASE, CINAHL, SCOPUS, the COCHRANE library and the Australian Indigenous HealthInfoNet. Articles were included where they: were published in English from 1990 onwards; described oral health outcomes for Indigenous adolescents aged 10 to 19 years; implemented a community based oral h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Culturally grounded models have been used and recommended as effective engagement and chronic disease prevention tools among American Indians [ 38 ]. Alaska Natives [ 39 ], and Australian Indigenous peoples [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Culturally grounded models have been used and recommended as effective engagement and chronic disease prevention tools among American Indians [ 38 ]. Alaska Natives [ 39 ], and Australian Indigenous peoples [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are challenges in Indigenous communities due to limited access to dental services, and barriers to health services in general, which include individual, organizational and policy level determinants [48]. Even though chair-side tests are easy to use and quick [49], in rural underserved Indigenous communities, prerequisite equipment and resources may be unavailable [48,50]. In addition, Indigenous Australians face many challenges and barriers in the utilization of oral health services, among them differences in perception of bene t within traditional health beliefs [48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that successful oral health interventions for Indigenous people globally adopted culturally safe, participatory and collaborative approaches [ 12 ]. It concluded that an effective program should employ local workers, utilise multiple settings and strategies and address the social, economic and cultural determinants of health [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found that successful oral health interventions for Indigenous people globally adopted culturally safe, participatory and collaborative approaches [ 12 ]. It concluded that an effective program should employ local workers, utilise multiple settings and strategies and address the social, economic and cultural determinants of health [ 12 ]. Despite this, few oral health research papers have explored social determinants of health in this context or established career development pathways for local workers despite many claiming to adopt a ‘capacity building’ approach [ 12 ].…”
Section: Introductionmentioning
confidence: 99%